Common financial problems for university students and ways of their reduction - Komarova, K. (ТДАТУ, 2018)
It should be mentioned that there are lots of ways to cope with financial problems, but the main reason of their existence is financial illiteracy. That‘s why, we think that extra courses on finance management should be organized not only for the TSATU students, but rather for the all members of our community.
Keywords: inflation; investors; rise of financial instability; field of education